THE INTEGRATION OF HISTORICAL VALUES, LOCAL CULTURE AND ELEMENTS OF ISLAM IN ASYURA RITUAL (TEN MUHARRAM) (International Conference on Social and Islamic Studies, 2022)
The basic reason for conducting this research arose when witnessing firsthand several local people welcoming and celebrating Ashura (tenth of Muharram) day. In the process there are unique things both in terms of history, the materials used, the symbols that are highlighted, the method of implementation, and other rituals that are not found in other societies with similar rituals. The main problem discussed is how to touch historical values, local culture, and Islamic elements in the Ashura ritual. This study aims to find out the touch of historical values, local culture, and Islamic elements in the Asyura ritual. Because this type of research is qualitative descriptive with an ethnographic approach, primary and secondary data sources were obtained by means of observation, in-depth interviews, and documentation. The results of the study show that it is very difficult for local people to solve the historical and local cultural elements of the rituals they perform even though it is a religious rite. The historical element is associated with historical events in the past where major disasters occurred which threatened the safety of lives so that people tried to prevent and anticipate them by carrying out rituals on Asyura Day. very classic and still imitate the traditions of his ancestors. Meanwhile, Islamic elements could be seen at that time, as well as the readings or prayers that were said during the Ashura (ten Muharram) rituals. Kata Kunci: Ritual, Sejarah, Budaya Lokal, dan Unsur Islam